Pengaruh Motivasi Terhadap Minat Investasi Mahasiswa FEBI UIN Mataram Pada Galeri Investasi Syariah UIN Mataram - Dewi Andiana; Muhammad Habibullah Aminy (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2019)
This study aims to analyze the Effect of Motivation on the Investment Interest of students of FEBI UIN Mataram at the UIN Mataram Islamic Investment Gallery. This type of research is associative with a quantitative method approach. This study employs descriptive research where the researcher wants to explain how to analyze the Effect of Motivation on the Investment Interest of Students of UIN Mataram in the Islamic Investment Gallery of UIN Mataram. The results of this study is based on data analysis and discussion that has been done previously, the motivational variable influences but is not positive and significant for investment interest. This can be seen from the results of the t-test which has a tcount of -. 203 with sig. t were 0.839 (p> 0.05). Result of coefficient of determination (R2) test obtained a value of 0.637, which means the contribution of the variance given by the Motivation variable to the dependent variable of investment interest in FEBI UIN Mataram students in the Islamic investment gallery UIN Mataram is 63.7%, while the remaining 36.3% influenced by variants or other variables outside this research model. This shows that the hypothesis in this study was rejected.